Sleeping Coach Mobile Application - Soo, Xin Yi; Nayef Abdulwahab Mohammed Alduais, (Applied Information Technology And Computer Science, 2024)
Mobile-based sleeping coach application was developed for the insomniac. This project was to assist insomniac when they are starting hard to falling asleep and staying asleep. Insomniac can be more easily to getting asleep with follow the sleep coach plan and using tools. Besides that, administrator module allows admin to edit sleep coach plans and sleep tests. This project was developed with Waterfall model, the chosen development tools to build up the system were Flutter, Visual Studio Code, and Firebase as database. The developed application provided several modules included administrator module which allow admin to edit plans, and tests, while user can choose the plan, answer sleep tests to get recommend plan, use tools, view the sleep diary, and produce report. Since the application did not have check list function and notification function, thus for future implementation, the application shall implement check list function, and notification function.